PENDAPATAN KONSUMEN : FAKTOR UTAMA PERMINTAAN KREDIT SEPEDA MOTOR PADA PT FEDERAL INTERNATIONAL FINANCE (FIF) CABANG PURWOKERTO - Agus Arifin (Faculty of Economics and Business Universitas Jenderal Soedirman, 2010)
The aim of this research is to know the effect of costumer income, costumer family consumption, price, interest, advance payment, and time expectancy of credit return toward credit demand of motorcycles sales in FIF Purwokerto. The method research is case study with logistic regression (logit) analysis. The results showed that : (1) Income, consumption, and time expectancy of motorcycle credit have significant effects; (2) Income has the bigest effect to credit demand of motorcycle because Wald score income variable bigger than its score of other variables. The implication of this research is to get credit, new costumers should think more about thier income factor.